Overview of Legislation on Ecological Taxation in Latin American Countries (Research, Society and Development, 2022)
Environmental taxation can be considered as a public policy instrument for sustainable environmental management, since it allows the government the possibility to manage actions that impact the environment, with resources from taxes, as well as influence the actions and conduct of taxpayers through benefits and rewards in the form of reduction, discounts, and tax credits. The present work aims to discuss the legal overview of environmental taxation in Latin American countries. This is a descriptive and exploratory study, in which the qualitative approach was adopted, through bibliographic research and documentary analysis of eight countries: Cuba, Guatemala, Haiti, Honduras, Nicaragua, Panama, Uruguay, and Venezuela. The results indicate that despite the existence of environmental legal provisions in the eight countries studied, only in Cuba and Venezuela, ecological taxes were found. It was also found that there were funds to finance environmental actions and programs in Nicaragua and Guatemala. However, it was not possible to confirm the implementation of a green tax policy integrated with the fulfillment of the Sustainable Development Goals (SDGs) foreseen in the 2030 Agenda. The study is considered relevant because it draws attention to the possibility of the adoption of tax instruments that assist in environmental preservation, for example with the institution of green or ecological taxation. The investigation is original because it tries to integrate the commitments of the SDGs with a view to the adoption of a green fiscal policy.